Antiplatelet Activity of Morus alba Leaves Extract, Mediated via Inhibiting Granule Secretion and Blocking the Phosphorylation of Extracellular-Signal-Regulated Kinase and Akt. (19th February 2014) - Kim, Dong-Seon; Ji, Hyun Dong; Rhee, Man Hee; Sung, Yoon-Young; Yang, Won-Kyung; Kim, Seung Hyung; Kim, Ho-Kyoung
Abstract : Ethnopharmacological Relevance . Morus alba L. leaves (MAE) have been used in fork medicine for the treatment of beriberi, edema, diabetes, hypertension, and atherosclerosis. However, underlying mechanism of MAE on cardiovascular protection remains to be elucidated. Therefore, we investigated whether MAE affect platelet aggregation and thrombosis. Materials and Methods . The anti-platelet activity of MAE was studied using rat platelets. The extent of anti-platelet activity of MAE was assayed in collagen-induced platelet aggregation. ATP and serotonin release was carried out. The activation of integrin α IIb β 3 and phosphorylation of signaling molecules, including MAPK and Akt, were investigated with cytofluorometer and immunoblotting, respectively. The thrombus formation in vivo was also evaluated in arteriovenous shunt model of rats. Results . HPLC chromatographic analysis revealed that MAE contained rutin and isoquercetin. MAE dose-dependently inhibited collagen-induced platelet aggregation. MAE also attenuated serotonin secretion and thromboxane A2 formation. In addition, the extract in vivo activity showed that MAE at 100, 200, and 400 mg/kg significantly and dose-dependently attenuated thrombus formation in rat arterio-venous shunt model by 52.3% (P < 0 .001 ), 28.3% (P < 0.01 ), and 19.1% (P < 0.05 ), respectively. Conclusions . MAE inhibit platelet activation, TXB2 formation, serotonin secretion, aggregation, and thrombus formation. The plant extract could be considered as a candidate to anti-platelet and antithrombotic agent.